LEGAL REMEDIES FOR PROTECTION OF ECONOMIC RIGHTS OF INDIVIDUALS IN ADMINISTRATIVE COURT AND OUT-OF-COURT PROCEDURES - Ustynova, Iryna; Moroz, Dariia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of this study is a comprehensive study of the regulatory and legal support of mechanisms for protecting the economic rights of individuals in the administrative court and other non-judicial institutions, and an analysis of the current regulatory framework for regulating the financial system of Ukraine. Research methods: the study was conducted using a system of general scientific and special scientific methods of cognition that provide an objective analysis of the subject under study. When studying this aspect, objectivity, value and structural-system approaches are important, as well as the use of logical techniques, in particular analysis and synthesis, comparison, generalization. Results: the key principles of judicial and non-judicial protection of citizens’ economic rights, as well as the structure of the mechanism for such protection in Ukraine, are identified. Discussion: the current state and features of the implementation of the mechanism for protecting citizens’ economic rights, as well as the search for prospects for further development of legislative means of protecting the economic rights of individuals, proposals are made regarding the introduction of the institution of a financial ombudsman in Ukraine, on conceptual research in financial law. Economic rights of individuals are fundamental rights guaranteed by the Constitution of Ukraine, which include the right to own, use and dispose of property, freedom of entrepreneurial activity, protection from arbitrary interference by the state in the sphere of private initiative and other elements of economic freedom. The mechanism for protecting the economic rights of individuals in Ukraine is implemented both within the framework of administrative proceedings and through extrajudicial institutions. The administrative court acts as the main instance for resolving disputes between citizens and subjects of power in the field of public finances, taxes, social payments, etc. Extrajudicial forms of protection, although less developed, also have the potential to effectively influence the observance of the economic rights of citizens. These include mediation institutions, the activities of the Commissioner for Human Rights of the Verkhovna Rada of Ukraine, the National Bank of Ukraine, as well as the promising model of the financial ombudsman, the introduction of which could fill the existing gaps in the field of alternative resolution of financial disputes. The current regulatory framework requires improvement in order to harmonize rights protection procedures with European approaches, in particular by simplifying citizens’ access to justice, reducing formalism in interaction with state authorities, and strengthening guarantees of impartial consideration of financial disputes.